An alternative subgeneric classification of Kalanchoe (Crassulaceae subfam. Cotyledonoideae) globally: a nomenclatural and taxonomic review, with a new status for K. subg. Pubescentes - Smith, Gideon F. (Phytotaxa, 2024)
In the most recently presented global synopsis of Kalanchoe (Crassulaceae subfam. Cotyledonoideae), which was published in 2003 by Bernard Marie Descoings (1931–2018), only two sections, K. sect. Kalanchoe [geographically widespread] and K. sect. Bryophyllum [geographically naturally limited to Madagascar, but with some species and nothospecies naturalised elsewhere], were recognised in the genus. Three years later, Descoings changed his views on the infrageneric classification of Kalanchoe when, in 2006, he published the subgenus name K. subg. Calophygia for a rather disparate group of species from virtually across the entire natural geographical distribution range of the genus. In this regard, Descoings built on and expanded the kalanchooid infrageneric concept that Sijfert Hendrik Koorders (1863–1919) put forward for Kalanchoe almost 90 years earlier. Apart from recognising K. subg. Calophygia in 2006, Descoings additionally upheld the autonymic K. subg. Kalanchoe and K. subg. Bryophyllum, both of which he recognised at the rank of section in 2003. The infrageneric classification of Kalanchoe that recognises primary diversity in the genus at the rank of subgenus, rather than at that of section, is now firmly entrenched. Following on from Descoings recognising three subgenera in 2006, the subgenus classification of Kalanchoe has recently been expanded with the publication of a further four subgenus names, in 2018 (K. subg. Kitchingia), in 2020 (K. subg. Fernandesiae), in 2023 (K. subg. Alatae), and in 2024 (K. subg. Pubescentes). The most up-to-date subgenus classification of Kalanchoe is presented here, with five subgenera recognised. With the exception of the geographically widespread K. subg. Kalanchoe, the four other subgenera are naturally endemic to Madagascar.